2003
DOI: 10.1161/01.cir.0000089083.61317.a1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Regulatory T Cell Type 1 Response Reduces the Development of Atherosclerosis in Apolipoprotein E–Knockout Mice

Abstract: Background— T helper type 1 (Th1) response plays a permissive role in atherosclerosis. We hypothesized that adoptive transfer of a novel subtype of T lymphocytes called regulatory T cells type 1 (Tr1) would inhibit Th1 responses by inducing a bystander immune suppression and therefore limit the development of atherosclerosis. Methods and Results— Clones of ovalbumin (OVA)–specific Tr1 cells expanded in vitro were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
172
0
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(192 citation statements)
references
References 42 publications
(47 reference statements)
5
172
0
11
Order By: Relevance
“…It has been shown that Tregs prevent atherosclerosis via TGF-β signaling and Tregs do not relieve the progression of atherosclerosis and inflammatory response if Tregs fail to respond to TGF-β signaling (15,32). Increased concentration of TGF-β and IL-10 was associated with suppressing pathogenic inflammatory responses, regulating immunity and promoting atherosclerotic plaque stabilization (33). On the contrary, deletion of TGF-β or IL-10 signaling accelerates atherosclerosis and plaque vulnerability (34,35).…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofmentioning
confidence: 99%
“…It has been shown that Tregs prevent atherosclerosis via TGF-β signaling and Tregs do not relieve the progression of atherosclerosis and inflammatory response if Tregs fail to respond to TGF-β signaling (15,32). Increased concentration of TGF-β and IL-10 was associated with suppressing pathogenic inflammatory responses, regulating immunity and promoting atherosclerotic plaque stabilization (33). On the contrary, deletion of TGF-β or IL-10 signaling accelerates atherosclerosis and plaque vulnerability (34,35).…”
Section: Tregs Are a Unique Subset Of T Cells Although The Number Ofmentioning
confidence: 99%
“…Activated TCRab + CD4 + cells constitute the dominant T lymphocyte population in vascular lesions and are mainly of the Th1 cell type. Natural regulatory T cells (Tregs) or induced peripheral Tregs efficiently inhibit experimental atherosclerosis development in several experimental models, whereas Treg depletion aggravates plaque formation (4). Accordingly, immune-mediated inflammation in atherosclerosis has been initially envisioned as solely orchestrated by T cells.…”
mentioning
confidence: 99%
“…These Th2 cells favor atherosclerotic plaque disruption/instability (Taleb et al, 2010a), a late event in atherosclerosis (Hansson, 2005). Induced Treg (iTreg), already described in Fig.2, protect mice from atherosclerosis and thus are anti-atherogenic (in yellow) (Mallat et al, 2003). Natural Treg -directly produced in the thymus− exert the same anti-atherogenic effect (Ait-Oufella et al, 2006).…”
Section: Cd4 + T Cell Subsets Sensitivity To Anti-thymocyte Globulinmentioning
confidence: 96%